2009
DOI: 10.1177/0146167209335640
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Courtship: Helping Friends Raise and Raze Relationship Barriers

Abstract: Do people help each other form romantic relationships? Research on the role of the social environment in relationship formation has traditionally focused on competition, but this article investigates novel patterns of cooperation within courtship interactions. Drawing on a functional/evolutionary perspective, women are predicted to cooperate primarily in building romantic thresholds and barriers; men are predicted to cooperate primarily in achieving romantic access. In support of these predictions, four studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Although an evolutionary perspective recognizes sexual and competitive motivations as undeniable aspects of human nature, it also emphasizes the roles of cooperation, love, and parental concern (e.g., Ackerman & Kenrick, 2009; Kameda & Tindale, 2006; Keltner, Haidt, & Shiota, 2006; Kenrick, 2006; Van Vugt & Van Lange, 2006). It is useful to keep in mind a point we made earlier: that sex is only a small part of human reproduction.…”
Section: Further Implicationsmentioning
confidence: 99%
“…Although an evolutionary perspective recognizes sexual and competitive motivations as undeniable aspects of human nature, it also emphasizes the roles of cooperation, love, and parental concern (e.g., Ackerman & Kenrick, 2009; Kameda & Tindale, 2006; Keltner, Haidt, & Shiota, 2006; Kenrick, 2006; Van Vugt & Van Lange, 2006). It is useful to keep in mind a point we made earlier: that sex is only a small part of human reproduction.…”
Section: Further Implicationsmentioning
confidence: 99%
“…One possible explanation for this is that although SSFs can assist in mate acquisition (Ackerman and Kenrick, 2009), they can also be competitors for mates. Having highly attractive friends may introduce costs that exceed the benefits of friendship with these individuals.…”
Section: The Evolutionary Psychology Of Friendshipmentioning
confidence: 99%
“…Anecdotal and experimental evidence supports the former possibility (e.g., self-sacrificial behavior to save fellow soldiers during wartime; also see the above citations), though less is known about the latter possibility. Although designed to test somewhat different hypotheses, Ackerman and Kenrick (2009) conducted a series of studies on intragroup and intergroup romance that have implications both for altruistic behavior and for the prospect of decreased male attraction toward female friends.…”
Section: Park and Ackerman 24mentioning
confidence: 99%
“…In a series of studies investigating cooperative courtship behaviors, Ackerman and Kenrick (2009) tested the possibility that friends would help each other to achieve romantic goals. The studies revealed that men and women in the U.S. did help their friends in ways akin to Park and Ackerman 29 the help given by kin in other cultures.…”
Section: Park and Ackerman 24mentioning
confidence: 99%
See 1 more Smart Citation